Will the current technological changes require new skills from CEOs? - Almeida, João Mendes Silveira de (2020)
Organizational behavior scholars have been studying the work of executives for more than a hundred years. Since Henri Fayol (1916), Mintzberg (1973 & 2013) and Tonelli and Alcadipani (2004), not many changes have been seen in the executives´ job. Words like Forecasting, Planning, Organizing, Commanding, Coordinating and Controlling, first mentioned by Fayol’s theory, are still present in their jobs. The few changes in the CEO’s activities are intriguing, considering the significant technological evolution that has happened in the world at the same time. Now, with the existing information technology inside the workplace, fully automated, computerized, and the digital applications used for surveillance and control; this study tried to understand, based on a qualitative approach, by interviewing ten Chief Executive Officers (CEO) in Brazil, the research question that guides this inquiry: Will the current technological changes require new skills from CEOs? A thematic analysis method was used in order to achieve these research results, which, in a few words, are: (1) Technological changes require new skills from the CEOs; (2) Human skills are predominant in the CEO's job; (3) Few changes have happened in the CEO's job; (4) The automation, computerization and surveillance processes require regulation; (5) Enterprise Social Media requires regulation. In addition, this work aims to benefit top management professionals, especially CEOs, human resource professionals and scholars of organizational behavior, more specifically those who seek to understand the impact of technology in the work of executives.